Pengaruh Ukuran Perusahaan dan Leverage Terhadap Kualitas Laba Pada Perusahaan Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2019 - 2022 - Widya Kurniawati (JURNAL RISET MANAJEMEN (JURMA), 2023)
This research aims to find out the impact of the size of the company and leverage on the quality of profit for the food and beverage companies listed on the Indonesia Stock Exchange in 2019–2022. Methods for collecting data with documentation techniques and downloading company financial statements through www.idx.co.id The research method used is quantitative statistics with the collection of data for the purpose of sampling, with a total sample of 17 companies. Data processing uses the SPSS 21 program, which includes classical assumption testing, descriptive analysis, double regression analysis, partial testing, and silmutan testing. The results of the t-test research showed that the size of the company has a positive impact on the quality of profits. The F test showed that the size of the company and leverage did not affect the quality of profits.